2001
DOI: 10.1002/tera.1066
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental exposure to methylene blue initiates teratogenesis in the mouse: Preliminary evidence for a mechanistic implication of cyclic GMP pathway disruption

Abstract: This study showed that transplacental exposure to MB is teratogenic in the mouse. Coadministration of ZPN prevented partly MB-induced teratogenesis, which supports the hypothesis that imbalance of cGMP pathway accounts, in part, for the teratogenicity of MB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…Importantly, MB has been associated with a high percentage of fetal intestinal atresia when used in the second trimester of pregnancy (Dolk, 1991; van der Pol et al, 1992; Gluer; 1995). In preclinical studies the intra-amniotic instillation of MB produced teratogenic effects including cleft palate, digit malformations, increased incidence of fetal mortality, and neuronal tube malformations (Iyengar and Lal, 1985; Tiboni et al, 2001). Intra-amniotic MB injection is currently not recommended in obstetrics due to its association with above mentioned teratogenic effects (for a review Cragan, 1999).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Importantly, MB has been associated with a high percentage of fetal intestinal atresia when used in the second trimester of pregnancy (Dolk, 1991; van der Pol et al, 1992; Gluer; 1995). In preclinical studies the intra-amniotic instillation of MB produced teratogenic effects including cleft palate, digit malformations, increased incidence of fetal mortality, and neuronal tube malformations (Iyengar and Lal, 1985; Tiboni et al, 2001). Intra-amniotic MB injection is currently not recommended in obstetrics due to its association with above mentioned teratogenic effects (for a review Cragan, 1999).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…It is therefore noteworthy that axial skeletal anomalies similar to those induced by L-NAME, resulted from in utero exposure to the soluble guanylate cyclase methylene blue (Tiboni and Lamonaca, 2001). In agreement with the postulation that methylene bluemediated teratogenesis was dependent at least partly on cGMP imbalance, co-treatment with the selective cGMPphosphodiesterase type V inhibitor zaprinast exerted protective effects by reducing by half the incidence of fetuses with axial skeletal defects and completely preventing neural tube defects, the other major malformation induced by methylene blue in the mouse (Tiboni and Lamonaca, 2001). Overall, data generated with L-NAME and methylene blue seem to suggest that abnormal development of the skeleton can be initiated not only by inhibition of NOS activity but also from disruption of the signaling pathway whereby NO mediates most of its biological actions.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence for the idea that sGC was important in development came from experiments where the sGC inhibitor methylene blue initiated teratogenesis in mice (neural tube defects, skeletal defects, etc.) [341,342]. Although methylene blue has multiple cellular effects beyond its ability to inhibit sGC, they also reported that co-administration of Zapronast, a phosphodiesterase inhibitor which will prolong the lifetime of cGMP, prevented the effect of methylene blue.…”
Section: B the Teratology Of Nomentioning
confidence: 95%